2005
DOI: 10.1097/01.moo.0000170525.74264.f8
|View full text |Cite
|
Sign up to set email alerts
|

Scar management: prevention and treatment strategies

Abstract: Despite optimal efforts to avoid scar formation, aberrant wound healing may occur. The use of topical agents and intralesional steroid injections can minimize early scar formation. Strategies for prevention and management of keloids and hypertrophic scars continue to develop, as the basic science mechanisms underlying aberrant wound healing are elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 45 publications
0
94
0
3
Order By: Relevance
“…Inhibitory SMAD 7 prevents phosphorylation of R-SMADs by forming stable associations with activated type I TGF-β receptors and thus provides negative feedback to the actions of TGF-β (56). Indeed, a potential therapeutic benefit of SMAD 7 overexpression has already been shown in bleomycin-induced lung fibrosis, postobstructive renal fibrosis and excessive cutaneous scar formation (57)(58)(59). SMAD 3 inhibition and SMAD 7 overexpression may thus be potential therapeutic targets to improve excessive scarring.…”
Section: Fibrogenic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory SMAD 7 prevents phosphorylation of R-SMADs by forming stable associations with activated type I TGF-β receptors and thus provides negative feedback to the actions of TGF-β (56). Indeed, a potential therapeutic benefit of SMAD 7 overexpression has already been shown in bleomycin-induced lung fibrosis, postobstructive renal fibrosis and excessive cutaneous scar formation (57)(58)(59). SMAD 3 inhibition and SMAD 7 overexpression may thus be potential therapeutic targets to improve excessive scarring.…”
Section: Fibrogenic Responsementioning
confidence: 99%
“…5-FU is a pyrimidine analog that is used as an antimetabolite in cancer chemotherapy (109). 5-FU is converted intracellularly to its active version, which was suggested to directly increase fibroblast apoptosis via inhibiting DNA synthesis preferentially in rapidly proliferating and metabolizing cells (58,139). In 1999, Fitzpatrick (140) was the first to report the use of 5-FU to effectively reduce scars during his 9-year experience, in which he administered more than 5000 injections to more than 1000 patients.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…In general, TGF-β1 and TGF-β2 physiologically promote fibroblast proliferation and collagen production in the proliferative phase of normal wound healing and have been found to be overproduced and unregulated in keloidal tissue. 112 In contrast, TGF-β3 appears to function as a scar inhibitor. 113 Animal studies have demonstrated promising results with topical application of TGF-β1 and TGF-β2 antagonists resulting in expedited reepithelialization and reduced scar formation and wound contraction in partial-thickness/full-thickness porcine burns as well as in rabbit skin excision models.…”
Section: Transforming Growth Factor-βmentioning
confidence: 99%
“…Yara iyileşmesi oldukça karışık ve mükemmel bir dengede ilerleyen fizyolojik olaylar dizisidir. Yara iyileşmesi sürecinde inflamasyon, proliferasyon ve maturasyon evreleri birbirini takip eder 11 . Granülasyon fazında makrofajlarda sitokin sentezler bunun sonucunda reepitelizasyon, kan dolaşımının düzenlenmesi ve yaralı dokunun güçlenmesi sağlanır 13 .…”
Section: Discussionunclassified
“…Bu nedenle cerrahi insizyon lokalizasyonunun seçiminde bu tip kaygılar önemli rol oynamıştır. Patolojik skar gelişimi görünümü itibariyle psikososyal etkileri olduğu kadar ağrı, kaşıntı ve gerginlik oluşturarak da yaşamı olumsuz etkileyebilmektedir 11 . Ancak genç yaş grubunda tek tip bir cerrahi insizyon sonrası oluşabilecek skar oluşumunu ve skar tipini etkileyebilecek olası risk faktörleri üzerine literatürde yeterli veri yoktur.…”
Section: Introductionunclassified